Pregnancy outcomes in women with mechanical prosthetic heart valves: a prospective descriptive population based study using the United Kingdom Obstetric Surveillance System (UKOSS) data collection system. (26th December 2016) - Vause, S; Clarke, B; Tower, CL; Hay, CRM; Knight, M; ,
Abstract : Objective: To describe the incidence of mechanical prosthetic heart valves (MPHV) in pregnancy in the UK; rates of maternal and fetal complications in this group of women, and whether these vary with the anticoagulation used during pregnancy. Design: Prospective descriptive population‐based study. Setting: All consultant‐led maternity units in the UK. Population: All women with an MPHV who were pregnant between 1 February 2013 and 31 January 2015. Methods: Collection and analysis of anonymous data relating to pregnancy management and outcome, using the UKOSS notification and data collection system. Main outcome measures: Maternal death, serious maternal morbidity, poor fetal outcome. Results: Data were obtained for 58 women giving an estimated incidence of 3.7 (95% CI 2.7–4.7) per 100 000 maternities. There were five maternal deaths (9%); a further 24 (41%) suffered serious maternal morbidity. There was a poor fetal outcome from 26 (47%) pregnancies. Only 16 (28%) women had a good maternal and good fetal outcome. Low‐molecular‐weight heparin (LMWH) was used throughout pregnancy by 71% of women. Of these, 83% required rapid dose escalation in the first trimester. Monitoring regimens lacked consistency. Conclusions: This study has estimated the incidence of MPHV in pregnant women in the UK. It includes the largest cohort managed with LMWH throughout pregnancy reported to date. It demonstrates a high rate of maternal death, and serious maternal and fetal morbidity. Women with MPHVs, and their clinicians need to appreciate the significant maternal and fetal risks involved in pregnancy. Care should be concentrated in specialist centres. Tweetable abstract: High rates of poor maternal and fetal outcomes in pregnant women with mechanical prosthetic heart valves Tweetable abstract: High rates of poor maternal and fetal outcomes in pregnant women with mechanical prosthetic heart valves